Regional growth and income patterns, 1960-65 - Martin, JP (Economic & Social Studies, 1971)
This study owes its origins to the earlier research of Ross and Baker into regional income and employment patterns in Ireland and to the appearance of the Buchanan Report in 1969. These works have laid much of the groundwork for future regional studies, but they have one basic methodological feature which may have outlived its usefulness for regional analysis in Ireland. This is the choice of the Irish county as the basic regional unit for analysis. This approach has had the merit of focussing attention on the economic problems of particular areas, such as the Western counties; yet it may have obscured the wider study of the relative economic performance and interrelationships of the economic regions in this country.
Keywords: Employment patterns - Ireland